The Violent Gift: Trauma’s Subversion of the Deuteronomistic History’s Narrative. By David Janzen - Poser, Ruth (The journal of theological studies, 2013)
While it might seem that the notion of trauma is commonplace in some contexts, ‘[t]he use of trauma theory in the field of biblical studies is’, as David Janzen puts it in his conclusion, ‘still in its infancy’ (p. 238). The study at hand, however, does a lot to let trauma theory grow into biblical hermeneutics. In it the Deuteronomistic History’s Narrative (Deuteronomy up to 2 Kings, DtrH) is consequently read as ‘trauma- literature’ or, to be more precise, as literature subverted by trauma. According to Janzen, DtrH as a whole aims at presenting a logical explanation of the 586 bce disaster.